The Inhibition and Resistance Mechanisms of Actinonin, Isolated from Marine Streptomyces sp. NHF165, against Vibrio anguillarum - Yang, Na; Sun, Chaomin (Frontiers in Microbiology, 2016)
Vibrio sp. is the most serious pathogen in marine aquaculture, and the development of anti-Vibrio agents is urgently needed. However, it is extreme lack of high-throughput screening (HTS) model for searching anti-Vibrio compounds. Here, we established a protein-based HTS screening model to identify agents targeting peptide deformylase (PDF) of Vibrio anguillarum. To find potential anti-Vibrio compounds, crude extracts derived from marine actinomycetes were applied for screening with this model. Notably, crude extract of strain Streptomyces sp. NHF165 inhibited dramatically both on V. anguillarum PDF (VaPDF) activity and V. anguillarum cell growth. And actinonin was further identified as the functional component. Anti-VaPDF and anti-V. anguillarum activities of actinonin were dose-dependent, and the IC50 values were 6.94 M and 2.85 M, respectively. To understand the resistance of V. anguillarum against actinonin, spontaneous V. anguillarum mutants with resistance against actinonin were isolated. Surprisingly, for the resistant strains, the region between 774 and 852 base pairs was found to be absent in the gene folD which produces 10-formyl-tetrahydrofolate, a donor of N-formyl to Met-tRNAfmet. When compared to the wild type strain, folD mutant showed 8 times of minimum inhibition concentration on actinonin, however, the folD complementary strain could not grow on the medium supplemented with actinonin, which suggested that folD gene mutation was mainly responsible for the actinonin resistance. To our knowledge, this is the first report showing that marine derived Streptomyces sp. could produce actinonin with anti-VaPDF activity and the resistance against actinonin by V. anguillarum is mediated by mutation in folD gene.